Traffic Unit Efforts In Handling Traffic Accidents Through Restorative Justice In The Jurisdiction of The Buleleng Resort Police - Made Dewi Saraningsih; Erikson Sihotang; I Nyoman Suandika (Return : Study of Management, Economic and Bussines, 2024)
The traffic unit's efforts to handle traffic accidents through restorative justice in the Buleleng Police jurisdiction include bringing the two parties involved together through mediation. This mediation process functions as a means to overcome the problems faced and find solutions. The police play a facilitative role by arranging meetings and presenting the best options to reach a fair resolution through restorative justice. Obstacles encountered in implementing relief for perpetrators of traffic violations through restorative justice efforts are: The perpetrator or victim of a traffic violation in the opposite direction cannot be present when the police handle the case, and there are no witnesses at the time of the traffic accident, this happened because of an accident. This traffic takes place in a quiet area and there is rarely any activity carried out by the community and there are no residential areas.